Effect of Ni and Co nanoparticle-doped ﬂux on microstructure of SAC305 solder matrix - Bashir, Muhammad Nasir; Haseeb, Abdul S.Md Abdul; Wakeel, Saif; Khan, Muhammad Ali; Quazi, Moinuddin Mohammed; Khan, Niaz Bahadur; Ahmed, Arslan; Soudagar, Manzoore Elahi M. (Springer, 2022)
Microstructure of the eutectic region and β-Sn grain of the solder matrix play an important role in the properties of the Sn-based solder joint. In the present study, Ni and Co nanoparticle (NP)-doped flux were added into the SAC305 solder matrix to observe their effect on the microstructure of the eutectic region and β-Sn grain during the reflow process. Results reveal that after the addition of Ni and Co NP-doped flux, the size of β-Sn grain and the size of IMC particles present in the eutectic region significantly reduced. The area of the eutectic region also increased. Reduction in size of β-Sn grain and IMC particles improves the mechanical and structural properties of the solder joint.